Effect of intimacy and dyadic coping on psychological distress in pancreatic cancer patients and spousal caregivers - Li, Jiarong; Liu, Linglong; Chen, Mingxia; Su, Wang; Yao, Tianying; Li, Xiaoxuan (Frontiers in Psychology, 2023)
Aims: The aim of this study was to investigate the effect of intimacy and dyadic coping on anxiety and depression in patients with pancreatic cancer and their spousal caregivers. Methods: This study conducted from October 2021 to June 2022, included 277 pancreatic cancer patients and their spousal caregivers. This research used actor-partner interdependence mediation model to explore the relationship of intimacy, dyadic coping and psychological distress among pancreatic cancer patients and their spousal caregivers. Results: The results of this study showed that there were two actor effects: the satisfaction of intimate relationship between pancreatic cancer patients and their spouse caregivers had a positive predictive effect on their dyadic coping (β=1.787, p < .001), (β=1.587, p < .001). The dyadic coping of pancreatic cancer patients and their spouse caregivers had a negative predictive effect on their own anxiety and depression (β=-0.253, p < .001), (β=-0.293, p < .001). The results of this study showed that there was a partner effect: intimate relationship satisfaction of pancreatic cancer patients had a positive predictive effect on dyadic coping of their spousal caregivers (β=0.574, p < .05). Conclusion: This study demonstrates the interdependence of pancreatic cancer patients and their spousal caregivers in coping with the disease. The healthy intimate relationship and effective dyadic coping styles are essential to alleviating disease pressure and lowering the psychological burden on cancer families.